Modeling of formaldehyde and nitrogen oxides from a proposed renewable energy biogas facility in Canada - Abdul-Wahab, Sabah Ahmed; Lohi, Ali; Yetilmezsoy, Kaan; Elkamel, Ali; Chan, Keziah (AMER INST PHYSICS, 2014)
The aim of this study was to use the CALPUFF modeling system, an effective and reliable atmospheric modeling tool, to predict the concentrations of formaldehyde (HCHO) and nitrogen oxides (NOx) released, due to the combustion of biogas in the combined heat and power (CHP) engines, from the Kawartha renewable energy generation facility at its proposed location in Ontario, Canada. In this study, HCHO and NOx were selected as the indicator and point source pollutants since they were the most significant products of biogas combustion emitted during the facility's normal operations (production of electricity and heat). The Lambert Conformal Conic projection coordinate system was implemented for the operation of the CALPUFF model. The proposed modeling scheme was coupled with both surface meteorological data (from 00:00 to 23:00) on an hourly basis and 12-h interval-based upper air meteorological data (from 00:00 to 12:00) to simulate the emission of these pollutants for the four seasonal Eastern Time meteorological conditions of winter (January 11-13, 2013), spring (April 14-16, 2013), summer (July 10-12, 2013), and autumn (November 16-18, 2013). The results from the CALPUFF dispersion model clearly demonstrated that the maximum 1-h average concentrations of both HCHO and NOx, emitted from the combustion of biogas (composed of 60% CH4 and 40% CO2) in five CHP engines (operation load = 100%, maximum electricity generation capacity = 9.8MW), were found to be within the limits defined by Ontario Regulation 419/05. (C) 2014 AIP Publishing LLC.
Keywords: AMBIENT AIR-QUALITY; METEOROLOGICAL CONDITIONS; PARTICULATE MATTER; DISPERSION; EMISSIONS; SO2; COMPLEX; APPORTIONMENT; MM5/CALPUFF; IMPACT; Science & Technology - Other Topics; Energy & Fuels